Is alanine aminotransferase level a surrogate biomarker of hepatic apoptosis in nonalcoholic fatty liver disease? - (:unkn) unknown (FUTURE MEDICINE LTD, 2010)
Aim: To evaluate the serum alanine aminotransferase (ALT) variabilities in nonalcoholic fatty liver disease (NAFLD) and correlate it with hepatocyte apoptosis and oxidative stress parameters. Methods: 24 patients with NAFLD and normal ALT were compared with 26 subjects with NAFLD and elevated ALT. Liver oxidative stress was estimated on the basis of malondialdehyde, superoxide dismutase and glutathione. Immunohistochemistry was performed for activated caspase 3 and 8, nuclear factor-kappa B, antiapoptotic Bcl-2 protein and serum TNF receptor levels were measured. Results: The mean caspase 3 and 8 activity scores, oxidative stress parameters, necroinflammatory grade and prevalence of severe fibrosis were comparable across the groups with normal versus elevated ALT. Patients with nonalcoholic steatohepatitis had significantly higher caspase 3 and 8 activity (percentage of cells with positive staining per high power field), and serum malondialdehyde (mmol/l) levels than those with simple steatosis. ALT elevation was not a risk factor for advanced necroinflammatory grade and fibrosis. A receiver operating characteristic curve did not demonstrate sensitivity and specificity for discriminative power of ALT. Conclusion: Apoptosis and oxidative stress are the main processes contributing to disease progression in NAFLD. ALT values do not correlate with the parameters of apoptosis and oxidative stress. The disease severity can only be determined by liver biopsy.
Keywords: alanine aminotransferase; apoptosis; nonalcoholic fatty liver disease; oxidative stress; NF-KAPPA-B; PARENCHYMAL-CELL APOPTOSIS; MITOCHONDRIAL DYSFUNCTION; HEPATOCYTE APOPTOSIS; INSULIN-RESISTANCE; CASPASE INHIBITOR; OXIDATIVE STRESS; DEATH RECEPTORS; STEATOHEPATITIS; INJURY